An ergonomic analysis of Malaysian elderly walking frame user posture - Hussain, Mohd Rizal; Ashari, Asmidawati; Ibrahim, Rahimah; Sulaiman, Ruhaizin (Universiti Putra Malaysia Press, 2022)
This study was to analyze walking frame user posture among the 15 participants of Malaysian elderly aged 60 and above in Selangor and Kuala Lumpur. This study utilized two postural observations and a computer simulation of the elderly user using Rapid Entire Body Assessment (REBA) and Rapid Upper Limb Assessment (RULA) analysis. The results revealed that the majority of respondents show a slightly bent posture, bowed their heads and appears difficulty during the use walking frame, which requires further investigation and appropriate techniques in the way the walking frame is used. Some recommendations were also suggested in this study.